Strong individual signatures and weaker group signatures in contact calls of Spix’s disc-winged bat, Thyroptera tricolor - Chaverri Echandi, Gloriana (2012)
Spix’s disc-winged bats, Thyroptera tricolor, form small, long-term social groups in which members are loyal to a patch of forest but move on a daily basis between highly ephemeral roosting sites (partly unfurled Heliconia leaves). This species has been shown to exchange social calls that facilitate contact with nearby bats and recruitment to roost sites. During flight, T. tricolor emits ‘inquiry’ calls that frequently elicit a response from individuals that have already entered a furled leaf. These ‘response’ calls are then followed by the flying bat entering the occupied leaf roost. In this study, we examined variation in the structure of inquiry and response calls, and assessed whether calls encode information about individual or group identity that would allow for acoustic discrimination to occur. We found that both inquiry and response calls were sufficiently consistent within individuals, and divergent between individuals, to permit separation of individual bats based on call structure. We also found some evidence for group-specific signatures, although these were less defined than differences observed between individuals. While this does not confirm that Spix’s disc-winged bats can discriminate between individuals and groups based on call information, our results indicate that both call types have a broad enough parameter space for this to occur.